2008
DOI: 10.1016/j.pt.2008.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Recent highlights in antimalarial drug resistance and chemotherapy research

Abstract: This review summarizes recent investigations into antimalarial drug resistance and chemotherapy, including reports of some of the many exciting talks and posters on this topic that were presented at the third Molecular Approaches to Malaria meeting held in Lorne, Australia, in February 2008 (MAM 2008). After surveying this area of research, we focus on two important questions: what is the molecular contribution of pfcrt to chloroquine resistance, and what is the mechanism of action of artemisinin? We conclude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 90 publications
0
61
0
2
Order By: Relevance
“…These observations are applied in vitro to modify protocols for the determination of parasite sensitivity to SP (25). Further studies have shown that probenecid can reverse P. falciparum resistance to several antifolates, including sulfadoxine and pyrimethamine, due to the reduction of folate influx into both red blood cells and parasites (8,16,18). In mammalian cells, MRPs have a role in folate homeostasis and have been shown to transport folate out of the cell (3,27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations are applied in vitro to modify protocols for the determination of parasite sensitivity to SP (25). Further studies have shown that probenecid can reverse P. falciparum resistance to several antifolates, including sulfadoxine and pyrimethamine, due to the reduction of folate influx into both red blood cells and parasites (8,16,18). In mammalian cells, MRPs have a role in folate homeostasis and have been shown to transport folate out of the cell (3,27).…”
Section: Discussionmentioning
confidence: 99%
“…falciparum has an endogenous folate biosynthesis pathway, but most strains can also use exogenous folate through the folate salvage pathway (17,23). The influx of exogenous folate (23) and the proteins responsible for this process (8,16,18), as well as efflux systems able to pump antifolate drugs out of the parasite intracellular space (16), have been proposed to further influence antifolate resistance.…”
mentioning
confidence: 99%
“…59 While a promising vaccine for malaria is currently in phase III trials, its efficacy appears to be in the order of 50%, 60 and thus malaria drugs are still critical to control and elimination programs. Artemisinin (ART) derivatives in combination with one or more longer acting antimalarial drug(s) of a distinct chemical class, for example lumefantrine, mefloquine or amodiaquine [2][3][4][5] (referred to as ART-based combination therapies, ACTs) are recommended for the treatment of uncomplicated P. falciparum malaria in most malaria-endemic areas and are arguably our last line of defense against this devastating disease.…”
Section: Resultsmentioning
confidence: 99%
“…In parasitic organisms, PCD has been described in the kinetoplastid trypanosomes (Ameisen et al, 1995;Welburn et al, 1996) and Leishmania (Arnoult et al, 2002;Bera et al, 2003;Zangger et al, 2002), the apicomplexan parasite Plasmodium Unicellular protozoan parasites cause a wide variety of human diseases. The current treatment of these infections is being challenged by an increasing incidence of drug resistance and a lack of effective vaccines (Croft et al, 2006;Fidock et al, 2008). The investigation of PCD pathways in these organisms might lead to the discovery of novel parasite control strategies (Alvarez et al, 2008;Deponte & Becker, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The current treatment of these infections is being challenged by an increasing incidence of drug resistance and a lack of effective vaccines (Croft et al, 2006;Fidock et al, 2008). The investigation of PCD pathways in these organisms might lead to the discovery of novel parasite control strategies (Alvarez et al, 2008;Deponte & Becker, 2004).…”
Section: Introductionmentioning
confidence: 99%